2022
DOI: 10.1038/s41698-022-00287-3
|View full text |Cite
|
Sign up to set email alerts
|

Small extracellular vesicle PD-L1 in cancer: the knowns and unknowns

Abstract: According to the conventional wisdom, programmed death protein 1 ligand (PD-L1)-mediated immunosuppression was based on the physical contact between tumor cells and T cells in the tumor microenvironment. Recent studies demonstrated that PD-L1 was also highly expressed on the surface of tumor cell-derived small extracellular vesicles (sEVs). PD-L1 on sEVs, which could also directly bind to PD-1 on T cells, has a vital function in immunosuppression and immunotherapy resistance. Due to the heterogeneity and dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…In addition, not all the injected αPD-L1 can permeabilize into tumors to be effectively utilized. Due to the small volume and large specific surface area of EVs, EV PD-L1 can easily enter deep tissues [ 26 ]. Thus, TEVs probably more efficiently decoy tumor-permeabilized αPD-L1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, not all the injected αPD-L1 can permeabilize into tumors to be effectively utilized. Due to the small volume and large specific surface area of EVs, EV PD-L1 can easily enter deep tissues [ 26 ]. Thus, TEVs probably more efficiently decoy tumor-permeabilized αPD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to TEVs, PD-L1 + EVs can also be produced by other types of cells. TEVs upregulate PD-L1 expression in tumor-associated macrophages [ 27 ], while plasma membrane PD-L1 of parent cells may be the major source of EV PD-L1 [ 26 ]. Therefore, tumor-associated macrophages with upregulated membrane PD-L1 probably secrete EVs with high levels of PD-L1, which may also contribute to the decoy and consumption of αPD-L1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that PD-L1 present on tumor cell-derived extracellular vesicles (sEVs) play a key role in immunosuppression and resistance to immunotherapies. Therefore, counteracting these vesicles could also improve conventional treatments [73].…”
Section: Nanoparticles and Lipid Vesiclesmentioning
confidence: 99%
“…The exosome is an sEV, defined by sizes of 30–150 nm in diameter. The roles of sEVs have been discussed in the context of progression and metastasis in various cancers [ 8 , 9 , 10 ]. sEVs are capable of transporting molecular cargo from one cell to another through vascular vessels and intercellular spaces.…”
Section: Introductionmentioning
confidence: 99%